2014
DOI: 10.15517/rbt.v62i4.13493
|View full text |Cite
|
Sign up to set email alerts
|

Development of RAPD-SCAR markers for Lonicera japonica Thunb. (Caprifolicaceae) variety authentication by improved RAPD and DNA cloning

Abstract: <p>Genetic diversity within a species is a common feature, which plays a vital role in its survival and adaptability, and is important for the identification and authentication of a species. <em>Lonicera japonica</em> is a traditionally used medicinal plant, which have been recently genetically characterized by an improved random amplified polymorphic DNA (RAPD) analysis. In this study, the molecular markers on the basis of these RAPD fragments have been developed to identify specific <em&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…A number of recent studies have reported the potential of traditional RAPD and improved RAPD for the genetic characterization and identification of different plant or animal species (Bhat et al, 2012;Kumla et al, 2012;Fu et al, 2013;Noormohammadi et al, 2013;Shakeel et al, 2013;Mei et al, 2014). When the RAPD technique is combined with the SCAR marker technology, specificity and stability is significantly improved, which makes genetic identification and authentication more convenient and efficient for testing different alleles (Rajesh et al, 2013;Yang et al, 2013Yang et al, , 2014Mei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have reported the potential of traditional RAPD and improved RAPD for the genetic characterization and identification of different plant or animal species (Bhat et al, 2012;Kumla et al, 2012;Fu et al, 2013;Noormohammadi et al, 2013;Shakeel et al, 2013;Mei et al, 2014). When the RAPD technique is combined with the SCAR marker technology, specificity and stability is significantly improved, which makes genetic identification and authentication more convenient and efficient for testing different alleles (Rajesh et al, 2013;Yang et al, 2013Yang et al, , 2014Mei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…White colonies were screened out by blue/white screening. The presence of the correct insert was verified by PCR amplification using the T7/SP6 primer pair (T7 primer: 5'-TAATACGACTCACTATAGGG-3', SP6 primer: 5'-ATTTAGGTGACACTATAGAA-3'), and by EcoRI digestion (Fu, 2012;Yang et al, 2013Yang et al, , 2014Fu et al, 2015). The cloned DNA fragments of the correct size were then sequenced by the Sanger method.…”
Section: Screening and Sequencing Of Inserted Dna Fragmentsmentioning
confidence: 99%
“…When RAPD is combined with SCAR, it can improve the stability and specificity, making genetic identification and authentication more efficient in studying different alleles. In our lab, we have successfully characterized a number of plant or fungal species by developing SCAR markers based on RAPD amplicons; namely Dimocarpus longan , Acorus species (Ryuk et al 2014), Lonicera japonica (Yang et al 2014), Trichoderma cf. harzianum (Pérez et al 2014), Cordyceps sinensis (Lam et al 2015), Litchi chinensis , Angelica sinensis , and Ganoderma lucidum (Khan et al 2016).…”
Section: Q19-22mentioning
confidence: 99%
“…A number of compounds that have been identified and isolated from Lonicera species, including biflavonoids, quercetin, phenolic acids, and dicaffeoylquinic acid, are supposed to be responsible for these various pharmacological and biological activities (Shang et al, 2011;Fu et al, 2013). L. confusa is known as Shan Yin Hua in markets, but its pharmacological components and biological activities might be different, and it is considered a substitute for L. japonica (Shang et al, 2011;Yang et al, 2014). In addition, L. japonica is more expensive than L. confusa.…”
Section: Discussionmentioning
confidence: 99%